2007
DOI: 10.1007/s00464-007-9614-0
|View full text |Cite
|
Sign up to set email alerts
|

Should surgical novices trade their retractors for joysticks? Videogame experience decreases the time needed to acquire surgical skills

Abstract: Previous VGE shortens time to achieve proficiency on two tasks on a validated surgical simulator. The possibility that VGE may ameliorate gender differences in length of time required to acquire surgical skills should be explored further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 8 publications
(10 reference statements)
0
48
0
Order By: Relevance
“…Shane et al evaluated 0.14 whether surgical novices exposed to previous video game exercises would acquire new surgical skills faster than nonplayers and concluded that previous video game exercises shortened the time to achieve proficiency on 2 tasks on a validated surgical simulator (12). In contrast to these studies, Harper et al collected information about the video game experiences of 242 preclinical medical students and chose 10 students with the highest and lowest video game exposure for closer examination to assess whether prior video game experience enhances the acquisition of robotic surgical skills.…”
Section: Discussionmentioning
confidence: 99%
“…Shane et al evaluated 0.14 whether surgical novices exposed to previous video game exercises would acquire new surgical skills faster than nonplayers and concluded that previous video game exercises shortened the time to achieve proficiency on 2 tasks on a validated surgical simulator (12). In contrast to these studies, Harper et al collected information about the video game experiences of 242 preclinical medical students and chose 10 students with the highest and lowest video game exposure for closer examination to assess whether prior video game experience enhances the acquisition of robotic surgical skills.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several reports have been published in this area in recent years. For example, Shane et al (11) showed that in a group of 26 medical students and first-year residents, individuals with previous video game experience took significantly less time to reach proficiency in laparoscopic skills than individuals without previous video game use. In 2 separate studies, Rosenberg et al (8) and Glaser et al (12) showed that in groups of 11 and 26 medical students, respectively, video game use correlated with both hand-eye coordination and reduced completion time for simple laparoscopic tasks.…”
Section: Discussionmentioning
confidence: 99%
“…25 Apart from the lack of haptic feedback, which the experienced group is accustomed to when in the operating room (OR), possible other explanations for the fact that performance on the PA task did not correlate with performance on the EP task include novices hypothetically having more videogame experience because they are younger and therefore acquire the skills needed to perform the simulated task faster. 26,27 In addition, from our data on quality of performance for the EP task, we hypothesized that novices might have performed faster than expected because they have limited insight into the possible complications of the procedure and therefore work less accurately.…”
Section: Figmentioning
confidence: 99%